(untitled) (Journal of Student Affairs in Africa, 2023)
This article discusses the nature of the professionalization of student affairs and services (SAS) in Africa by analyzing the discourses evident and legitimated through the Journal of Student Affairs in Africa (JSAA). The analysis is driven by three research questions: What is the extent of the journal’s engagement with the terms profession, professionalism, professional, and professionalization? How are these terms used in the journal and how do these uses relate to the social justice imperative in SAS? Overall, the analysis shows that the professionalization discourse in JSAA draws strongly on notions that certain professional traits and high-level knowledge and skills must be possessed by SAS personnel for the field to be professionalized. Furthermore, the analysis reflects a stronger social justice discourse than a discourse on SAS as a profession. Finally, this article considers opportunities for a scholarship on the development of SAS as a profession.